CASTEP investigation of FeS and FeSe: Structural, electronic, optical, and mechanical properties using the HSE03 hybrid - Geoffrey Tse (AIP Advances)
This study analyzed the structural, electrical, optical, and mechanical characteristics of iron chalcogenides (FeS and FeSe). Theoretical investigations were conducted using first-principles calculations using density functional theory. According to our band structure plot, the compounds were identified as narrow-bandgap semiconductors. The respective bandgaps of FeS and FeSe are 0.497 eV [0.545 eV for generalized gradient approximation (GGA)] and 0.425 eV (0.465 eV for GGA). The dielectric function was calculated using the Ambroxol–Sofos and Kramers–Kronig theory for optical properties. Meanwhile, the mechanical properties were evaluated with a second-order stress–strain relationship. In this study, the compounds were brittle and ionic–covalent. Young’s, shear, and bulk moduli were impacted when the S atom was replaced with Se in the iron-based compounds. In addition, the elastic constants Cij decreased. These numerical findings suggest potential applications for iron-based compounds in UV absorbers and optoelectronic devices.